Exploring Front-line nurses’ loyalty in Covid-19 Emergency wards: a Grounded Theory study Exploring Front-line nurses’ loyalty in Covid-19 Emergency wards: a Grounded Theory study - Lara Pierboni; Domenica Gazineo; Riccardo Triani; Pamela Bagli; Lea Godino (Dissertation Nursing)
Background. Front-line Covid-19 nurses developed a sense of belonging and professional loyalty to the newly established Covid-19 wards, often resisting a return to their original wards after the first wave.